2022
DOI: 10.1038/s41590-022-01370-4
|View full text |Cite
|
Sign up to set email alerts
|

A genetic disorder reveals a hematopoietic stem cell regulatory network co-opted in leukemia

Abstract: The molecular regulation of human hematopoietic stem cell (HSC) maintenance is therapeutically important, but limitations in experimental systems and interspecies variation have constrained our knowledge of this process. Here, we have studied a rare genetic disorder due to MECOM haploinsufficiency, characterized by an early-onset absence of HSCs in vivo. By generating a faithful model of this disorder in primary human HSCs and coupling functional studies with integrative single-cell genomic analyses, we uncove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 68 publications
(87 reference statements)
2
26
0
Order By: Relevance
“…In this context, it has been reported that Evi1 functions as a major positive regulator of HSC self‐renewal divisions, 14 increasing HSC proliferation and blocking myeloid differentiation 17 , 18 . Haploinsufficiency of Evi1 leads to reduced self‐renewal of LT‐HSCs in mice, which correlates with the clinical observation of rare early‐onset bone marrow failure syndromes associated with near‐complete depletion of HSCs 19 . These syndromes have been observed neonatally or early in childhood in humans who carry heterozygous loss of function mutations in the MECOM locus 20–22 .…”
Section: Evi1 In Normal Hematopoiesismentioning
confidence: 86%
See 2 more Smart Citations
“…In this context, it has been reported that Evi1 functions as a major positive regulator of HSC self‐renewal divisions, 14 increasing HSC proliferation and blocking myeloid differentiation 17 , 18 . Haploinsufficiency of Evi1 leads to reduced self‐renewal of LT‐HSCs in mice, which correlates with the clinical observation of rare early‐onset bone marrow failure syndromes associated with near‐complete depletion of HSCs 19 . These syndromes have been observed neonatally or early in childhood in humans who carry heterozygous loss of function mutations in the MECOM locus 20–22 .…”
Section: Evi1 In Normal Hematopoiesismentioning
confidence: 86%
“…[20][21][22] In engineered models of this disease, haploinsufficiency of EVI1 results in the collapse of an HSCspecific transcriptional network consisting of hundreds of genes, suggesting that EVI1 is a master epigenetic regulator of functional identity in these cells. 19 Evi1 gain of function models similarly illustrates an important role for Evi1 in HSC biology, with lentiviral overexpression of Evi1 in primary murine hematopoietic progenitor cells leading to a block in differentiation and prolonged survival of myeloblasts in long-term culture. 23 However, in this study, the authors also observed a cytostatic effect caused by the inhibition of cell cycle progression, which the authors interpret as being consistent with Evi1 enforcing the important feature of quiescence upon HSCs.…”
Section: Evi1 In Normal Hematopoiesismentioning
confidence: 97%
See 1 more Smart Citation
“…MDS1-EVI1 comprises an N-terminal so-called PRDF1-RIZ homology domain, two C2H2 zinc finger DNA binding domains, one at the N-terminus including seven zinc fingers, and the other at the C-terminus including three zinc fingers, a proline-rich repressor domain and a small aspartate/glutamate-rich acidic region located in the C-terminal region (Figure 2) (37). MECOM acts as crucial transcription factor in hematopoiesis, playing an important role in the formation and self-renewal of long-term hematopoietic stem and progenitor cells (HSPCs) (38) as well as myeloid differentiation through interaction with transcription factors including GATA1 (39), SPI1 (40), RUNX1 (41) and others (42). The inversion or translocation of chromosome 3 drives inv(3)/t(3;3) AML via structural rearrangement of an enhancer that upregulates transcription of EVI1.…”
Section: Mecom Deficiency Serves As An Example Of a Genotype-phenotyp...mentioning
confidence: 99%
“…Primary cell culture CD34+ HSPCs were thawed into a maintenance medium consisting of a StemSpan II base (StemCell Technologies), CC100 (StemCell Technologies), 50 ng/mL human TPO (Pepro Tech), and 1% penicillin/streptomycin (Life Technologies). 61,62 Cells treated with RNP complexes for enhancer deletions were electroporated 48 hours after thawing and collected 72 hours post-nucleofection. Cells treated with lentivirus were transduced 24 hours after thawing, sorted 72 hours after thawing, and moved to erythroid media 96 hours after thawing.…”
Section: Enrichment and In-silico Functional Studymentioning
confidence: 99%